Sistem Pencarian Dokter Spesialis Kandungan Dengan Toko Perlengkapan Bayi Di Kota Surabaya Secara Mobile - Fery Setyawan; Noven Indra Prasetya; Firman Hadi S Pratama (Informatics Engineering Department-UWKS, 2017)
The need for online information is also required for patients with obstetricians. Most pregnant women rely on obstetric health services that are located far away from their homes and there is not necessarily any obstetrician on duty. In addition, lack of information about the nearest obstetrician as well as not knowing the doctor's office hours. This makes pregnant women reluctant to conduct regular checkups and check the symptoms of gynecological diseases, so pregnant women late to perform medical actions that can lead to things that are not desirable. For that we need a new breakthrough in finding information Specialist Physicist The nearest content that can be accessed by mobile. Therefore, a system that is able to display information about physician location, practice time and location of baby supplies can be accessed by mobile. This information system displays two information systems location that is the location of the doctor and the location of the baby gear shop. The doctor's location information system displays the location, address, doctor's name, phone number and doctor's office hours. In the information system the location of the baby supplies store location, opening and closing hours, the name of the store and equipped with a display list of goods sold by the store. This system is made as attractive as possible with a user-friendly view that allows users to use it.